Avaliação de modelos de microturbina a gás single shaft para estudos de microgeração distribuída com cogeração térmica - Rauber, Jeremy Gustavo (2016)
The overwhelming need to use renewable energy sources for electricity generation allowed the use of gas microturbines (MTG) in distributed generation applications (GD) and energy cogeneration. Microturbine behavior prediction for studies applied in this context require the use of dynamic models. Among the many microturbines existing gas in the literature, we selected three dynamic models of gas microturbines: recurrent in the literature, Rowen model; the simple model, GAST model; a model representative of the thermodynamic equations, thermomechanical model. However, lack of studies to represent the same microturbine under the same ways using different types of microturbines and seeking to establish parametric relationships so that they can check for any correlation between them and there is few studies on the impact of the use of simplified models MTG in DG and CHP applications. For work on the gas microturbine literature, typically address the problem of GD and energy cogeneration separately. This work aims to contribute analysis on the applicability of MTG models for simultaneous studies of GD and energy cogeneration, seeking to find correlation between the equations and parameters governing such models and elucidate the impact of simplifications in MTG models for studies of GD and cogeneration. These models were evaluated for possible analytical and parametric relationships to each other, as well as to their static and dynamic operating characteristics. The microturbine was considered connected to the mains via a frequency inverter and operating in cogeneration energy represented by a Stirling engine by performing heat recovery from the exhaust gases. The first evaluation of models and simplifications was performed qualitative and comparative manner, elucidating the main differences modeling each MTG model. It was later performed static analysis of the equations that predict the torque and temperature. Finally, the application of models in GD and cogeneration with the aid of dynamic simulation involving tests that induced MTG to changes in the operating point of electricity generation, as well as the system's response to an electrical failure in the network scenario was evaluated. The analysis of the simulation results showed that the three models of microturbines make up three different philosophies of modeling that have no direct algebraic relations between them, but have parametric relationships. The main difference between the results of different models modeling the micro turbine s fuel system. Based on the results obtained, Gast model showed similar results to model more Rowen, unlike thermomechanical model. The simplifications of dynamic models of MTG were sensitive to the consideration of the fuel system, because its absence influences the representation of cogeneration and GD phenomena.